Efikasi Herbisida Campuran Atrazin Dan Mesotrion Untuk Mengendalikan Gulma Pada Budidaya Tanaman Jagung ( Zea Mays L.) - Dera Fungky Ellezandi; Dad R.J. Sembodo; Herawati Hamim (Jurnal Penelitian Pertanian Terapan, 2016)
Maize (Zea mays L ) is the most important food crops in the world beside rice and wheat.  Weeds are one factor cause decrease productivity of maize.  The objectives of this research were to know of dose combination atrazine and mesotrione herbicide to control the weed in maize field and how was the atrazine and mesotrione effect to maize.  The research was conducted in Natar, South Lampung and Weeds Laboratory Faculty of Agriculture, University of Lampung, from December 2014 to April 2015.  The experiment was arranged in Completely Randomized Block Design (CRBD) with six treatments and four replications.  The treatments are combination atrazine and mesotrion herbicide rates at 500+50; 750+75; 1000+100; 1250+125; and 1500+150 g ha-1, mechanical weeding, and control.  Homogenity of variance was tested by Bartlett test and additivitty tested by Tukey's test, the comparison of mean were tested by Least Significant Difference (LSD) test at 5% level.  The result showed that (1) Atrazine and mesotrione herbicide at 500+50 until 1500+150 g ha-could suppress total, sedges, Cyperus rotundus and Celosia argenthea weed at 3 Weeks After Treatment (WAT), whereas at 6 WAT couldn’t suppress weeds.  (2) Atrazine and mesotrione herbicide at 500+50 until 1500+150 g ha-could suppress broadleaves, Richardia brasiliensis and Commelina benghalensis weeds until 6 WAT.  (3) Atrazine and mesotrione herbicide at 500+50 until 1500+150 g ha-couldn’t suppress grasses and Rottboellia exaltata weed until 6 WAT  (4) Atrazine and mesotrione herbicide does not affect the growth and production of maize. Key words: Weed, Efficacy, Atrazine, Mesotrione, Maize